Distance Lesson Study in Mathematics: A Case Study of an Italian High School - Capone, Roberto; Adesso, Maria Giuseppina; Fiore, Oriana (Frontiers in Education, 2022)
The COVID-19 pandemic put teachers and students in virtual classrooms, necessitating the Lesson Study to be adapted to such a new context. In this paper, we investigate how the roles of teachers, observers, and students are changing, considering the use of Information and Communication Technology (ICT) as the only medium of communication. The research methodology is based on the Documental Approach to Didactics, including Instrumental Genesis. It is a qualitative internal case study. The data was collected through video analysis. The Lesson Study (LS) methods were based on a cyclic model (co-planning, teaching, observation, debriefing, and revision), adapted to Distance Learning (DL). The topic is about Statistics, starting from the COVID-19 diffused data. The experimental work allowed us to observe the inter-connections between LS and DL. We deduced that ICT could be considered as a resource for the documental genesis, which generates processes aimed at social knowledge mediated by the teacher. We supposed that the observing phase was less invasive than during virtual experimentation. Nevertheless, the observers had difficulties understanding some students' and teachers' emotional aspects and analyzing the group activities. The technological resources were an added value for the LS. We present an LS methodology, entirely carried out through DL. The main value consists of showing both affordability and constraints of the DL with respect to the LS and vice versa.